280 Prospective international observational registry of patient at risk for atherothrombotic events: the French data. (23rd September 2015) - Sabouret, P; Dallongeville, J; Steg, P G; Cacoub, P; Krempf, M; Mas, J L; Pinel, J F; Priollet, Pascal; Taminau, Denis; Gattolliat, O; Herrmann, M A; Montalescot, G
Abstract : Objectives: To evaluate the control of cardiovascular risk factors at 1 year follow-up and the therapeutic strategies in French patients, recruited in the REACH international registry, with several cardiovascular risk factors (CVRF) or suffering from established atherothrombotic disease (EAD). Methods: The REACH registry has included patients, aged at least 45 years, and with several cardiovascular risk factors (CVRF) (>3), or suffering from established atherothrombotic disease (EAD: patients with coronary artery disease (CAD), with cerebrovascular disease (CVD), and patients with lower limb peripheral arterial occlusive disease (PAD)). In France, 713 investigators selected 4740 patients, with either CVRF (n=1226) or with EAD (n=3514) between December 2003 and June 2004. After exclusion of patients with missing data, 2916 patients (26.4% CVRF) were available for statistical analyses. Results: Among the 2916 french patients of the REACH registry, 1169 (40.1%) suffered from CAD, 317 (10.9%) had documented CVD, 257 (8.8%) suffered from PAD, and 13.8% had symptomatic polyvascular disease. The rate of control of major CV risk differs between groups: target goals are obtained for 3.6% for patients with CVRF only, 20.9% for patients with monovascular disease, 15.2% for patients with polyvascular disease (two or three locations). Table 1 Rate of patients at targets (No smoking, Glycemia<1.26 g/l, SBP/DBP<140/90-130/80 mmHg if diabetes, Total Cholesterol<2.0 g/l) Tobacco=0 BP control Diab TC<2 g/l All CVRF CVRF 84.2% 12.1% 61.7% 46.4% 3.6% Monovascular disease 90.2% 41.2% 78.3% 56% 20.9% Polyvascular disease 85.3% 35.4% 78.9% 50% 15.6% p χ 2 <0.0001 <0.0001 <0.0001 <0.0001 <0.0001 χ 2 : χ 2 analysis; BP, blood pressure; Diab, diabetes with glycemia<1.26 g/l; TC, total cholestérol; CVRF, cardiovascular risk factors. Table 2 The rate of treated patients also differs between groups. ASA Statin βblock ACE ARB CVRF 30.4% 61.1% 30.8% 37.7% 33.7% Monovascular disease 62.9% 73.6% 51.4% 38.3% 22.2% Polyvascular disease 46.6% 77.6% 44.6% 46% 19.5% p χ 2 < 0.0001 <0.0001 <0.0001 <0.011 <0.0001 p χ 2 : χ 2 analysis; ASA, acetyl salycilic acid; βblock, β-blockers; ACE, angiotensin-converting enzyme inhibitors; ARB, angiotensin receptors blockers. Conclusion: The rate of patients treated and controlled is globally poor, with significant differences between patients according to the number of symptomatic arterial beds. Same findings are observed for treatment strategies. These results underline the need for more widespread use of medications, and for optimise therapeutic education to induce lifestyle changes. Educational program will be evaluate. Objectifs: Evaluer le contrôle des facteurs de risque cardiovasculaire et les stratégies thérapeutiques chez les patients français présentant soit des facteurs de risque CV (FRCV), soit une maladie athérothrombotique établie. Méthodes: Le registre REACH a inclus des patients âgés d'au moins 45 ans, présentant des facteurs de risque cardiovasculaire(FRCV) (> 3), ou souffrant d'une maladie athérothrombotique établie (MAE: après un événement documenté de maladie coronaire, cérébrovasculaire, ou souffrant d'une artériopathie oblitérante des membres inférieurs (AOMI)). En France, 713 médecins investigateurs ont sélectionné 4740 patients, présentant soit des FRCV (n=1226) soit une MAE (n=3514) entre décembre 2003 et juin 2004. Après exclusion des sujets avec des données biologiques manquantes 2916 patients (26.4% FRCV) étaient disponibles pour les analyses. Résultats: Parmi les 2916 patients français du registre REACH, 1169 (40.1%) avaient une maladie coronaire, 317 (10.9%) avaient une maladie ischémique cérébrovasculaire, 257 (8.8%) avaient une AOMI documentée et 13.8% une affection polyartérielle. Le pourcentage des patients contrôlés pour tous les facteurs de risque varie selon les caractéristiques: 3, 6% pour les patients du groupe FRCV, 20, 9% s'il existe une seule localisation athérothrombotique, et de 15, 2% s'il y a 2 ou 3 localisations athérothrombotiques. Table 1 Pourcentage de patients contrôlés (Tabac sevré, Glyc < 1.26 g/l, PAS/PAD < 140/90–130/80 mmHg si diabète, Cholestérol<2.0 g/l). Tabac HTA Diab CT<2 g/l Tous FR FRCV 84.2% 12.1% 61.7% 46.4% 3.6% MAE monoartérielle 90.2% 41.2% 78.3% 56% 20.9% MAE polyartérielle 85.3% 35.4% 78.9% 50% 15.6% p < 0.0001 <0.0001 <0.0001 <0.0001 <0.0001 Table 2 Le pourcentage des patients traités varie selon les caractéristiques également. ASA Statin βblock ACE AAII FRCV 30.4% 61.1% 30.8% 37.7% 33.7% MAE monoartérielle 62.9% 73.6% 51.4% 38.3% 22.2% MAE polyartérielle 46.6% 77.6% 44.6% 46% 19.5% p < 0.0001 <0.0001 <0.0001 <0.011 <0.0001 ASA, acetyl salycilic acid; βblock, β-bloquants; ACE, angiotensin-converting enzyme inhibitor; AAII, antagonistes des récepteurs AT1 de l'angiotensine II. Conclusion: Le pourcentage de patients traités et contrôlés est globalement faible et varie selon le statut des patients. Le même constat est effectué pour les traitements validés. L'éducation thérapeutique et la mise en place des stratégies thérapeutiques validées nécessitent d'être optimisées. Ces résultats associés aux données publiées sur les patients français du registre pourraient servir de support aux campagnes de sensibilisation sur le risque cardiovasculaire. Le suivi sur 4 ans permettra de juger de l'évolution des pratiques et des événements CV majeurs.